2020
DOI: 10.17129/botsci.2398
|View full text |Cite
|
Sign up to set email alerts
|

Environmental filters determine the distribution of tree species in a threatened biodiversity hotspot in western Mexico

Abstract: Background: Analyzing interactions between vegetation and environmental factors at regional scales provide information for the understanding of species assemblages. Hypotheses: Environmental restrictions at higher elevations produce a decreasing species richness pattern along an elevational gradient and the climatic variables related to temperature and precipitation are the main filters of species distribution. Objectives: (1) To identify the different assemblages of tree species occurring in a bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 90 publications
2
16
0
Order By: Relevance
“…Such a pattern was also found in the western region of Mexico for tree species (Olvera-Vargas et al 2010) and in a study of six genera of the Mexican cloud forest (Alcántara et al 2002). This pattern corresponds to the one described by Guo et al (2013) for trees, and to the study of Arenas-Navarro et al (2020) who found a similar pattern in Serranias Meridionales of Jalisco for Quercus species.…”
Section: O N L I N E F I R S Tsupporting
confidence: 82%
See 1 more Smart Citation
“…Such a pattern was also found in the western region of Mexico for tree species (Olvera-Vargas et al 2010) and in a study of six genera of the Mexican cloud forest (Alcántara et al 2002). This pattern corresponds to the one described by Guo et al (2013) for trees, and to the study of Arenas-Navarro et al (2020) who found a similar pattern in Serranias Meridionales of Jalisco for Quercus species.…”
Section: O N L I N E F I R S Tsupporting
confidence: 82%
“…Finally, we want to point out that the number of altitudinal zones, species turnover points, and the richness pattern found in this study depend on the method being used (Bach & Gradstein 2011), the site of study (Mastreta-Yanes et al 2018) and the analyzed taxa (Arenas-Navarro et al 2020). However, a similar altitudinal pattern and altitudinal zones could be possibly found in the case of temperate taxa and those associated with oaks in the SMS.…”
Section: Ii)mentioning
confidence: 53%
“…The mean annual temperature ranges from 28.5 to 30.6 • C; the annual precipitation ranges from 1500 to 1800 mm, with 80% of the rainfall concentrated between June and October [42]. The main vegetation types are tropical deciduous forest at low elevations, passing through oak forest, pine-oak forest, montane cloud forest in glens and fir forest at high elevations [33,43]. The Serranías Meridionales of Jalisco is a biodiversity hotspot, with many tree species, including several endemic species of Quercus and Pinus, among others [44,45], and this could be one of the regions with the highest oak species richness in the world, reaching up to 30 oak species [33,46].…”
Section: Study Sitementioning
confidence: 99%
“…Based on previous woody tree plot surveys across the region (33 rectangular plots, 0.1 ha; [33]), we were able to locate 21 oak species along the study area and we proceeded to measure functional traits on them. In each plot, we quantified the leaf and stem traits associated with resource uptake and water-use strategy between five and 15 adult individuals of each oak species, sampling a total of 275 individuals belonging to the 21 oak species (Table 1).…”
Section: Leaf and Stem Trait Measurementsmentioning
confidence: 99%
“…MTemWarQua and MTemColQua depict the extreme of temperature across the year that may act as abiotic filters selecting for specific sets of species adapted to those temperature conditions. MAnnPre and PreSeaso are key variables that depict the sum of water availability across the year but also how this varies temporally, which has been shown to strongly determine plant and animal distributions (Arenas‐Navarro et al, 2020; Zamora‐Gutierrez et al, 2018). As the results of different climate models may differ (Pierce et al, 2009), we followed the approach from Aguirre and collaborators (Aguirre‐Gutiérrez et al, 2017) to account for such variability in climate projections for the RCP 2.6 and 8.5.…”
Section: Methodsmentioning
confidence: 99%